Peer Counselor Training Untuk Mencengah Perilaku Bullying - Salmiati Salmiati; Rosmawati Rosmawati; Mardi Lestari (Indonesian Journal of Learning Education and Counseling, 2018)
The study examines the application of peer counselor training to prevent bullying behavior. This study uses the Tru-experimental design experimental research approach. The research design used was pretest-posttest control group design with research subjects as many as 60 students, 30 students for the control group and 30 students for the experimental group. There are two instruments used: bullying questionnaire and peer counselor training questionnaire. The results obtained through questionnaire behavior on bullying behavior were analyzed using descriptive statistical analysis showing differences in student bullying behavior between before and after the implementation of peer counselor training, namely from high categories to moderate categories. While the results of inferential statistical analysis using the t-test showed a real or positive influence on the application of peer counselor training to prevent student bullying behavior.